2001
DOI: 10.1089/10966200152744481
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Anthocyanin Extract from Purple Black Rice

Abstract: Antioxidant activity was studied for anthocyanins extracted from purple black rice (PBR) by a 3% aqueous trifluoroacetic acid solution (TFA), as well as for anthocyanins extracted from blueberry (Bluetta, high bush type). Capillary zone electrophoresis revealed that the PBR extract contained almost exclusively a single anthocyanin, which was identified as cyanidin 3-O-beta-D-glucoside (Cy 3-Glc) after purification by polyvinylpyrrolidone column chromatography. In contrast, 11 anthocyanins were identified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
129
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(136 citation statements)
references
References 17 publications
2
129
0
5
Order By: Relevance
“…This finding is consistent with a previous study indicating that the proanthocyanidins and γ-tocotrienol are significantly higher in RRE than those of the BRE, whereas in BRE content α-tocotrienol and α-tocopherol are higher than those of the RRE. In addition, the anthocyanin derivative cyanidin-3-Oglucoside is mainly found in BRE, as well as a small amount of peonidin-3-O-glucoside, which is similar to other reports 14,15 . Our study shows that phenolic Values represent mean ± SD.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with a previous study indicating that the proanthocyanidins and γ-tocotrienol are significantly higher in RRE than those of the BRE, whereas in BRE content α-tocotrienol and α-tocopherol are higher than those of the RRE. In addition, the anthocyanin derivative cyanidin-3-Oglucoside is mainly found in BRE, as well as a small amount of peonidin-3-O-glucoside, which is similar to other reports 14,15 . Our study shows that phenolic Values represent mean ± SD.…”
Section: Discussionsupporting
confidence: 89%
“…[28][29][30][31] We developed a method for the analysis of bilberry anthocyanins by CZE, and showed that this method is useful for the analysis of anthocyanins from different sources 13,26) and also for studies of their chemical reactivity. 27) However, in the previous study, minor anthocyanins with galactose and arabinose as the conjugated sugar remained unidentified due to several reasons, including the lack of authentic reference samples, insufficient CZE detection limits and relatively smaller amounts of these anthocyanins in the bilberry extract.…”
Section: Disucussionmentioning
confidence: 99%
“…7,8) As with other flavonoids, the phytoceutical significance of anthocyanins has been discussed in relation to a wide range of physiological functions such as vision improvement, 9,10) anticancer activity, 11,12) and antioxidant activity. [13][14][15][16][17] Capillary electrophoresis (CE) has been successfully used in addition to HPLC to analyze flavonoids. [18][19][20][21][22][23][24][25] As we showed previously, capillary zone electrophoresis (CZE) is especially useful for the analysis of anthocyanins in extracts of fruits 26) and colored rice, 13) because the silica capillary tube used in CZE is applicable to samples like these that have not been purified.…”
mentioning
confidence: 99%
“…Black rice contains macro-and micronutrients such as carbohydrate and protein, and the micronutrients such as vitamins and minerals which are higher than those in white rice. Kristamtini et al (2012) and Ichikawa et al (2004) reported that the mineral content of black rice such as Fe, Zn, Mn and P is higher than white rice, and that the mineral content in black rice depends on the variety and type of soil where it is grown. In addition to the nutrient contents, black rice also contains bioactive compounds including anthocyanin.…”
Section: Introduc Onmentioning
confidence: 99%